Adolescent's subjective perceptions of chronic disease and related psychosocial factors: highlights from an outpatient context study. Issue 1 (December 2016) - Santos, Teresa; de Matos, Margarida; Marques, Adilson; Simões, Celeste; Leal, Isabel; Machado, Maria
Abstract Background Adolescents with chronic disease (CD) can be more vulnerable to adverse psychosocial outcomes. This study aims: 1) to identify differences in psychosocial variables (health-related quality of life, psychosomatic complaints, resilience, self-regulation and social support) among adolescents who feel that CD affects or does not affect school/peers connectedness (measured by self-reported participation in school and social activities); and 2) to assess the extent to which psychosocial variables are associated with connectedness in school and peer domains. Methods A cross-sectional study was conducted in 135 adolescents with CD (51.9% boys), average age of 14 ± 1.5 years old (SD  = 1.5). Socio-demographic, clinical, and psychosocial variables were assessed, using a self-reported questionnaire, which included the Chronic Conditions Short Questionnaire, KIDSCREEN-10 Index, Symptoms Check-List, Healthy Kids Resilience Assessment Module Scale, Adolescent Self-Regulatory Inventory, and Satisfaction with Social Support Scale. Descriptive statistics, GLM-Univariate ANCOVA and Logistic Regression were performed using the IBM Statistical Package for Social Sciences (SPSS), version 22.0. The significance level was set atp  < 0.05. Results Thirteen to eighteen percent of the adolescents felt that CD affected participation at school (PSCH) and participation in leisure time with friends (PLTF). These adolescents presented lower results for all psychosocial study variables, when compared with adolescents who did not feel affected in both areas of participation. From the studied psychosocial variables, the most important ones associated with PSCH (after controlling for age, gender, diagnosis, and education level of father/mother) were self-regulation and psychosomatic health. Concerning the PLTF, social support was the sole variable explaining such association. Conclusions The present study pointed out the association between psychosocial variables; and living with a CD and school/peers connectedness. The need to focus on the assessment of the effects of a CD on adolescents' lives and contexts is suggested, as well as on the identification of vulnerable adolescents. Such identification could help to facilitate the maximization of social participation of adolescents with CD, and to plan interventions centered on providing support and opportunities for a healthy youth development. For that purpose, a complex and multifactorial approach that includes clinicians, schools, family, and peers may be proposed.